(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Agriculture employs more than 80% of the population of Burkina Faso and contributes nearly 40% to the Gross Domestic Product (GDP). rainfed agriculture and occupy an important place because the crop employs nearly 4 million people and contributes more than 4% to GDP and about 14% of export earnings in recent years (AICB (2023a).The area sown in 2016-2017 are estimated at nearly 740,000 ha, and the production was estimated at nearly 683,000 tons of seed cotton with relatively low yields of less than one ton per hectare (AICB (2023b). The cotton sector has experienced a significant decline in recent years producing 407,308 tons with yields of 655 kg/ha during the 2022-2023 agricultural season (AICB (2008).This situation can be explained, among other things, by uncertain climatic conditions (rainfall and temperature) and damage due to crop pests (AICB (2008).